Implementasi Model Problem Based Learning (PBL) Untuk Meningkatkan Kompetensi Desain Pembelajaran Fisika Mahasiswa - Rahim, Abd (Universitas Pahlawan Tuanku Tambusai, 2024)
The aim of the study was to analyze the competence of students' physics learning designs between students whose learning used the PBL model and conventional learning. The research method used is an experimental research method with a one group pretest-posttest design. The sample in this study were Physics Education study program students who attended a Physics Learning Design course at one of the tertiary institutions in Jambi. Data collection instruments in the form of tests and questionnaires. The test was used to determine the cognitive aspects of students' physics learning design competence before treatment (pre-test) and after being treated (post-test) using the PBL model, and questionnaires were used to find out student activities during lectures. The data obtained were analyzed using a 2-way ANOVA statistical test. Based on the description of the results and discussion, students taught using the PBL model obtained an average score of 73.8, and conventional 62.4 overall. Dasamping that, based on the results of the calculation of the hypothesis test using 2-way ANOVA at a significance level of 0.05 obtained Fcount is 20.03, while Ftable is 3.99. Because Fcount > Ftable, the working hypothesis is accepted. In accordance with the acceptance criteria, the working hypothesis reads; there are differences in the competence of students' physics learning designs before treatment (pretest) and after treatment (posttest) using the model (PBL) are accepted. This means that students who are taught using the PBL model can improve the competence of student physics learning designs compared to conventional learning.